The authority of everyday objects : a cultural history of West German industrial design - Betts, Paul (Weimar and now, 2004)
From the Werkbund to the Bauhaus to Braun, from furniture to automobiles to consumer appliances, twentieth-century industrial design is closely associated with Germany. In this pathbreaking study, Paul Betts brings to light the crucial role that design played in building a progressive West German industrial culture atop the charred remains of the past.